Sanitasi Rumah Penderita Tubercullosis Paru - Kadarusman, Haris; Sutopo, Agus; Hasan, Amrul (MIDWIFERY JOURNAL, 2024)
Background : Pulmonary Tuberculosis is still become issue problem health in Indonesia and Indonesia is the second country the biggest after India in matter amount pulmonary tuberculosis sufferer  as well as spread in a way wide throughout Indonesia. One of the factors related to close with occurrence and spread Pulmonary TB disease is a Home Sanitation Factor .Objective : It is known condition sanitation House sufferer Pulmonary Tuberculosis in the work area Health Center Hajimena Year 2024.Method : Study done with do observation and measurement condition sanitation House sufferer as well as do interview to sufferer Tuberculosis . Types of research descriptive with respondents 16 people with pulmonary tuberculosis in the Health Center area Hajimena . Analysis of the data used is Uni Variat, for variable Lighting, Temperature, Humidity and area room Sleep use Minister of Health Regulation Number 2 of 2024, concerning Regulation Implementation Regulation Government Number 66 of 2014 concerning Environmental Health, whereas For variable ventilation, enclosure and housing room based on literature .Results : For variable Lighting, Temperature, Bedroom Size  part big Not yet No fulfil Conditions and ventilation, Cage distance, Number of residence room Still Not yet good for humidity room part big Already fulfil terms and conditions big own ceiling .Conclusion : Sanitation House sufferer Tuberculosis in the Health Center Area Hajime No Good Keywords : Home Sanitation, Tuberculosis, Condition